Individual and neighbourhood socioeconomic status increase risk of avoidable hospitalizations among Canadian adults: A retrospective cohort study of linked population health data - Wallar, Lauren E; Rosella, Laura C (International Journal of Population Data Science, 2020)
Introduction Avoidable hospitalizations refer to acute care use for conditions that should normally be managed inprimary care settings. Lower socioeconomic status that is often measured using area-based indicators(e.g. median household income) has been shown to increase risk of avoidable hospitalizations.However, both area- and individual-level socioeconomic status can contribute to hospitalization risk,but previous data limitations have prevented separate analyses. Further, the joint effect of individualand neighbourhood socioeconomic status has not been established in the Canadian population. Toaddress this, this study links individual-level household income and neighbourhood-level materialdeprivation data within a population-based Canadian cohort. Objectives To determine the individual and joint effect of individual-level household income and neighbourhood-level material deprivation on risk of hospitalization for a set of chronic ambulatory care sensitiveconditions using linked health survey, hospital discharge, and census-derived data. Methods A pooled cohort was created by linking sociodemographic and health information from eight cycles ofthe Canadian Community Health Survey (2000/2001 - 2010) to hospital discharge records and Cana-dian Marginalization Indices (2001, 2006) (N = 354,595). The primary outcome variable was riskof index hospitalization with a primary diagnosis of angina, asthma, congestive heart failure, chronicobstructive pulmonary disease, diabetes, epilepsy, or hypertension. The primary exposure variablewas joint individual-level national household income quintile and neighbourhood-level material de-privation quintile. Relative risk (RR) was estimated by constructing modified Poisson regressionmodels with robust error variance. Results In fully adjusted models with income and deprivation considered separately, individuals in the lowesthousehold income quintile and highest material deprivation quintile were at increased risk of hospi-talization (Income RR: 1.82 (95% CI 1.56-2.13) Deprivation RR: 1.67 (1.44-1.95)). When incomeand deprivation were jointly considered, those with low individual income living in high deprivationneighbourhoods were at greatest risk of hospitalization (RR 1.83 (95% CI 1.63 - 2.05)). Conclusions Both individual income and neighbourhood deprivation separately and jointly increase risk of avoid-able hospitalizations. Additional research is needed to understand their mechanisms of action.However, both levels should be considered when designing effective policies and interventions toreduce avoidable hospitalizations.